The Eucharistic words of Jesus - Jeremias, Joachim; Perrin, Norman (London, UK SCM, 1966)
Includes bibiographical references and indexes.
Translation of "Die Abendmahlsworte Jesu"
Keywords: Jesus -- Last supper; Eucharist